2021
DOI: 10.1016/j.jse.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after a Grammont-style reverse total shoulder arthroplasty?

Abstract: Background: The purpose of this study was to determine the factors associated with outcomes after reverse total shoulder arthroplasty (RTSA). Methods: We retrospectively evaluated all RTSAs performed by the senior author between January 1, 2007, and November 1, 2017. We evaluated pain visual analog scale (VAS), Simple Shoulder Test (SST), and American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) scores and complication and reoperation rates at a minimum of 2-year follow-up. We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…These results are consistent with findings in the previously reported literature on functional outcomes and ROM after RTSA. 9 , 10 Cabarcas et al. 9 performed a systematic review that showed a mean postoperative ASES score of 75.0 in patients undergoing RTSA for rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with findings in the previously reported literature on functional outcomes and ROM after RTSA. 9 , 10 Cabarcas et al. 9 performed a systematic review that showed a mean postoperative ASES score of 75.0 in patients undergoing RTSA for rotator cuff tear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it increased the lever arm of the deltoid muscle, allowing for elevation strength recovery [1][2][3]. The Grammont prosthesis warranted excellent clinical outcomes and a low revision rate [4,5]. These favorable results led surgeons to expand its indications from exclusively addressing rotator cuff tear arthropathy to encompassing fractures and their sequelae, primary osteoarthritis, avascular necrosis, post-traumatic osteoarthritis, and even cases of irreparable rotator cuff tears [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The unintended consequences were medial scapular notching and decreased external rotation. Today, proponents of the medial center of rotation generally obtain good results [9], but concerns about scapular notching and decreased ROM have guided others to explore the merits of lateralization [2,5] and even use a more varus neck-shaft angle.…”
mentioning
confidence: 99%